Anti-KCNQ1 K+ channel autoantibodies increase IKs current and are associated with QT interval shortening in dilated cardiomyopathy - Li, Jin; Seyler, Claudia; Wiedmann, Felix Tobias; Schmidt, Constanze; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Cardiovascular research, 2013)
Autoimmune-associated proarrhythmia in dilated cardiomyopathy (DCM) is poorly understood. Given the significance of KCNQ1 potassium channels in heart rhythm disorders, we hypothesized that circulating anti-KCNQ1 autoantibodies directly modulate cardiac electrophysiology in DCM patients. The purpose of this pilot study was to characterize ion channel autoantibodies in DCM targeting the cardiac repolarizing K+ current, IKs, and the underlying KCNQ1 potassium channel.One hundred and fifty DCM patients were screened for anti-KCNQ1 autoantibodies using an enzyme-linked immunosorbent assay. Autoantibodies targeting the extracellular pore domain of the KCNQ1 channel were detected in 6% of study patients. Seropositive individuals exhibited significantly shorter corrected QT intervals when compared with seronegative patients (371 ± 39.9 ms vs. 408 ± 47.9 ms; P = 0.036). There was no difference in clinical severity of heart failure between groups. The functional significance of anti-KCNQ1 antibodies was determined in human embryonic kidney 293 cells expressing KCNQ1/KCNE1 using the whole-cell patch clamp technique. IKs recordings demonstrated a 2.7-fold increase in mean current density on exposure to patients' sera containing anti-KCNQ1 antibodies in contrast to seronegative controls (8.74 ± 1.44 pA/pF vs. 3.26 ± 0.36 pA/pF; P = 0.003). IKs enhancement was not associated with increased KCNQ1 protein levels or altered cell surface expression of the channel.Anti-KCNQ1 autoantibodies found in a subgroup of DCM patients are associated with QT interval shortening and increased IKs current.